2015
DOI: 10.7860/jcdr/2015/13973.6580
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stress During Antenatal Period Among Pregnant Women in Tertiary Care Hospital of Southern India

Abstract: Individual as well as pregnancy related factors can contribute to perceived stress in pregnant women. With the established relationship between maternal mental health, pregnancy outcome and infant growth, the assessment and management of stress early in the pregnancy is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
1
29
1
2
Order By: Relevance
“…This is in contradiction with other studies where poor population was found to be more stressed. [17][18][19][20][21][22] According to the authors the reason for low stress among pregnant women with low socio-economic status might be attributed to the fact that they are accustomed to harsh and challenging circumstances, making them more adaptive and efficient during maternal period as compared to the group of women with high socio-economic status whose routine life is simpler than their maternal period.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contradiction with other studies where poor population was found to be more stressed. [17][18][19][20][21][22] According to the authors the reason for low stress among pregnant women with low socio-economic status might be attributed to the fact that they are accustomed to harsh and challenging circumstances, making them more adaptive and efficient during maternal period as compared to the group of women with high socio-economic status whose routine life is simpler than their maternal period.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prevalence of stress in pregnant women, a previous study showed that approximately 15-25% of pregnant women experience antenatal anxiety or mood disorders (Alderdice, McNeill, & Lynn, 2013). Vijayaselvi et al (2015) reported a mean perceived stress score of 13.5 ± 5.02, which occurred in the majority of groups (102, 65.4%); 57.7% of the total sample was primigravida. Some conditions known to cause stress during pregnancy include smoking, fear of complications, and physiological changes (Obel, Hedegaard, & Henriksen, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Some conditions known to cause stress during pregnancy include smoking, fear of complications, and physiological changes (Obel, Hedegaard, & Henriksen, 2005). In addition, unplanned pregnancy and spouse's occupational status are also a strong factor related to stress in pregnant women (Vijayaselvi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…19 Various factors such as an unplanned pregnancy, lack of social support, societal pressures, difficult working conditions, and or deficiency in economic resources might serve as stress inducers for an expecting woman. 20,21 Research has continually indicated that stress experienced by the mother during pregnancy is harmful to the baby's health and development. 22,23 Whether this stress also influences the attachment bond between the mother and her unborn baby is the research question that the current study aims to answer.…”
Section: Introductionmentioning
confidence: 99%